Local Labour Market Outcomes of Educational Migration - Rokita-Poskart, Diana; Adamska, Małgorzata (Zielona Góra: Faculty of Economics and Management Press)
Thus far, the majority of studies have focused on international student migration. Less attention has been paid to internal migration for tertiary education and even less to local effects caused by this category of migration. To redress this limitation, the paper determines the most important consequences of internal migration for university enrolment in the local labour market of a university city. This is shown through the example of the Polish university city with one of the highest student-to-population ratios - Opole.
Keywords: university cities; educational migration; local labour market; labour supply; labour demand